Work - family conflict, family - work conflict , and job satisfaction : a study among married women in thenmaradchi divisional secretariat - Sritharan, V.; Sritharan, S. (Vavuniya Campus, 2022)
The present study tests the effect of work/family conflict on the job satisfaction relationship. In contrast to previous studies that have examined the effects of work/family conflict on the job satisfaction. The present study focuses on the work/family conflict on the job satisfaction of Thenmaradchi divisional secretariat. As hypothesized, we found that the use of work/family conflicts were predictive of job satisfaction. In addition, the present results of the correlation and regression analyses showed that both effects are possible. There is a negative relationship between work/family conflict and job satisfaction. The author observed a direct effect of work/family conflict in the prediction of job satisfaction ; according to the result of multiple regressions, family to work conflict and work to family conflict has a significant impact on job satisfaction. Whereas family to work conflict has greater impact on job satisfaction than work to family conflict. Our research extends previous research in a number of ways. We believe that a particular strength of our study is that if incorporated the data gathered at different points in time and from more than one source.
Keywords: Work family conflict; Family work conflict; Job satisfaction